A Study on Impact of Performance Management Systems on Employee Performance and Motivation in Private Sector Banks in Thiruvarur District of Tamilnadu - N Subathra; M. Sethuraman (Academic Bright Collaboration, 2026)
Performance Management Systems (PMS) have become a critical tool for enhancing employee efficiency and aligning individual performance with organizational goals in the banking sector. However, few empirical studies have focused on the differential impact of PMS across demographic and job-related variables in private sector banks, particularly in semi-urban regions such as Thiruvarur District, Tamil Nadu. This study aims to examine the impact of PMS on employee performance and motivation, while analyzing variations based on gender, age, experience, and occupational status. This study is based on primary data collected from 175 employees working in private sector banks using a structured questionnaire. Statistical tools such as percentage analysis, independent sample t-tests, ANOVA, and chi-square tests were employed to evaluate the relationships between PMS and employee-related outcomes. The findings indicate that over 70% of respondents perceive PMS as positively influencing their performance, competency development and knowledge enhancement. The independent sample t-test revealed statistically significant differences (p < 0.05) between male and female employees in terms of performance and competency levels. ANOVA results confirm significant variations across age and experience groups, indicating that the effectiveness of PMS is not uniform across all the employee categories. Furthermore, chi-square analysis establishes a strong association between occupational status, department, and employee perceptions of PMS effectiveness. The study concludes that while PMS plays a significant role in improving employee performance and motivation, its impact varies across demographic and organizational factors. These findings highlight the need for context-specific and differentiated PMS strategies rather than a uniform approach. This study contributes to the existing literature by addressing the gap in region-specific empirical evidence and providing insights for enhancing PMS design in private sector banks.